2022
DOI: 10.18805/ijare.a-5846
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Correlation and Path Analysis in Cowpea [Vigna unguiculata (L.) Walp]

Abstract: Background: Cowpea [Vigna unguiculata (L.) Walp] is a self pollinated crop, belonging to family fabaceae and sub family papilionaceae. It is an important multipurpose grain legume extensively cultivated in arid and semi arid regions of Sub-Saharan Africa, Asia, Central and South America. The assessment of variability present in any crop species is an essential pre requisite for formulating an effective breeding programme, as the existing variability can be used to enhance the yield level of cultivars after fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…Pod length was positively and highly significantly correlated with each of the characters the number of pods/plant, the number of seeds/pod, plant height, and grain yield/plant, while it was correlated significant and negatively with grain index. In a genetic investigation, it was discovered that pod length significantly increased seed yield (Kumar et al, 2016), and prior investigations by (Kutty et al, 2003;Anbumalarmathi et al, 2005;and Suganthi & Murugan, 2008) found similar results, which were consistent with the current study. It is possible to increase grain output by enhancing this trait.…”
Section: Pod Length (Cm)supporting
confidence: 91%
“…Pod length was positively and highly significantly correlated with each of the characters the number of pods/plant, the number of seeds/pod, plant height, and grain yield/plant, while it was correlated significant and negatively with grain index. In a genetic investigation, it was discovered that pod length significantly increased seed yield (Kumar et al, 2016), and prior investigations by (Kutty et al, 2003;Anbumalarmathi et al, 2005;and Suganthi & Murugan, 2008) found similar results, which were consistent with the current study. It is possible to increase grain output by enhancing this trait.…”
Section: Pod Length (Cm)supporting
confidence: 91%
“…Adults lay eggs singly on soil near the root zone of the crop (Oza et al, 1996). Larvae feed on the root hairs and on root nodules whereas adult beetles feed on leaves, buds and leaves and also on the buds and flowers of pigeon pea (Gupta and Singh, 1981;Gowda et al, 2006 andPrathapan, 2016). During the rainy season, this pest has been noticed in Vigna spp., Glycine spp., Phaseolus spp., Cajanus cajan and as a vector of bean southern mosaic virus (Reddy and Verma, 1986;Swaminathan et al, 2012).…”
Section: Managementmentioning
confidence: 99%
“…Adults lay eggs singly on soil near the root zone of the crop (Oza et al, 1996). Larvae feed on the root hairs and on root nodules whereas adult beetles feed on leaves, buds and leaves and also on the buds and flowers of pigeon pea (Gupta and Singh, 1981;Gowda et al, 2006 andPrathapan, 2016). During the rainy season, this pest has been noticed in Vigna spp., Glycine spp., Phaseolus spp., Cajanus cajan and as a vector of bean southern mosaic virus (Reddy and Verma, 1986;Swaminathan et al, 2012).…”
Section: Managementmentioning
confidence: 99%